INTERNATIONAL DEBATER’S POLITENESS STRATEGY IN INTERLANGUAGE PRAGMATICS OF REQUEST - Bahtiar, Jessica Yunanda (Annual International Conferences on Language, Literature, and Media, 2022)
The study aims to investigate the speech acts of international debaters in the 2022 Asian English Olympics in giving requests. This study focuses on the request speech acts and the politeness strategy produced by international debaters with different cultural backgrounds. This study used a qualitative approach because it observed the request speech acts of international debaters in applying the politeness strategy. There were four participants, consisting of Uzbekistan, Philippines, Hong Kong, and Malaysian debaters. The data contained the requests delivered by the international debaters conducted through WhatsApp messenger, both group and private messages. In collecting the data, the researcher was a part of the participants in the debate competition. Thus, the researcher could collect the data in the private group made special for the participants who joined the debate competition. Additionally, the researcher's relationship with the participants was the opponent of the debate team. Finally, it is found that the request speech acts by showing a demand, command, and force expression. Thus, politeness strategy, social distance in which, status and relationship, and background impact the way of giving requests.